THE ROLE OF PHYSICAL ACTIVITY IN THE MANAGEMENT OF ENDOMETRIOSIS: A LITERATURE REVIEW - Karolina Marrodán-Wojtczak; Paulina Krzeszowska; Adrianna Zajączkowska; Jakub Zajączkowski; Jan Wilk; Kacper Stępniak; Jakub Jarmołowicz; Aleksandra Kujawa; Karolina Krochmal; Radosław Kuźma (International Journal of Innovative Technologies in Social Science, 2025)
Background: Endometriosis is a chronic gynecological disorder characterized by ectopic endometrial tissue, leading to inflammation, chronic pelvic pain and reduced quality of life. While hormonal and surgical treatments remain standard, interest in non-pharmacological interventions, including physical activity, has grown due to its potential anti-inflammatory, analgesic, and psychosocial benefits. Purpose: To evaluate the impact of physical activity on the course of endometriosis Material and Methods: Information was collected using the english language literature databases such as PubMed and GoogleScholar. The literature from 1985-2025 was reviewed to evaluate the pain management in endometriosis. Specific attention was paid to publications on the impact of physical activity and exercises on endometriosis associated pain and the quality of life. Results: The reviewed literature consistently indicated that physical activity contributed to a reduction in endometriosis-related symptoms, most notably chronic pelvic pain. Despite methodological heterogeneity, all studies reported either clinical or statistically significant benefits of PA in endometriosis symptom management. However, several authors emphasized the need for further standardized, large-scale trials to determine optimal exercise type, duration, and intensity. Conclusions: Physical activity appears to be a promising complementary therapy for managing endometriosis symptoms, particularly pain and fatigue, by modulating inflammation, stress responses, and hormonal balance. While current data are encouraging, further high-quality, longitudinal studies are required to establish standardized exercise protocols and confirm long-term benefits.